ICT as Alternative Model for Poverty Reduction in Nigeria: An Appraisal of the Telecom Revolution - OROKPO, Ogbole F.E.; NGARA, Christopher Ochanja (International Journal of Publication and Social Studies, 2017)
The objective of this paper is to assess the impact of ICT, particularly, the telecommunications revolution on poverty reduction in Nigeria. Using historical approach spiced with empirical observation, the paper argues that previous poverty reduction initiatives adopted by successive governments in Nigeria failed to yield the desired result because the ICT was neglected as a critical and strategic component. The paper contends that with the massive impact of the telecom revolution on the Nigerian economy as well as its remarkable contributions to poverty reduction in terms of employment generation and creation of value chains within a relatively short-time frame in Nigeria, the ICT appears to offer more viable and sustainable option to poverty reduction than previous approach. The paper concludes that to sustain the gains of the telecom revolution in Nigeria particularly in the face of increasing globalization, there must be concerted efforts by the government, development partners and indeed all stakeholders to deploy the use of ICT in all sectors of the national economy in order to enhance productivity and reduce poverty.